2011
DOI: 10.3109/09553002.2011.544372
|View full text |Cite
|
Sign up to set email alerts
|

Perception of quality of life of a cohort population years after relocation from previous low-dose radiation exposure in Co-60 contaminated buildings in Taiwan

Abstract: More than 10 years after being informed of radiation exposure, the exposed populations were observed to have significantly lower perception of HRQoL even though no biomedical effects were apparent. It is recommended that appropriate intervention be carried out in the follow-up of post-event rehabilitation for the radiation exposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In some patients who cured with radio therapy, memory deficits [35], depression [36]. Social and psychological disorders [37] can be observed. This damage can be explained in different ways as follow.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients who cured with radio therapy, memory deficits [35], depression [36]. Social and psychological disorders [37] can be observed. This damage can be explained in different ways as follow.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the damage effect of radiation may be delayed for months due to "delayed acute reactions". The most important factor for determining the extent of injury in a tissue is its ability to repopulate after radiation damage [15][16][17][18]. The dividing stem cells and nondividing functionally mature cells are involved in the process of tissue repopulation.…”
Section: Radiation Effects and Interactions With The Biological Systementioning
confidence: 99%
“…A previous study indicated that the exposed population exhibited significantly lower health-related quality of life (HRQoL) scores in the physical, psychological, and social relationship domains than did unexposed members of the general population in the same city (Yen et al 2011). Furthermore, the HRQoL scores were similar amongst those who were exposed to various amounts of cumulative radiation, and women and those who were informed of the exposure at or before the age of 12 years demonstrated relatively lower HRQoL scores (Yen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, depression is a well-known independent predictor of inferior HRQoL amongst patients with chronic diseases (Chung et al 2009, Cruz et al 2010. Therefore, we attempted to elucidate the prevalence and determinants of depression amongst the members of the RCB cohort, which demonstrated low HRQoL scores in the study of Yen et al (2011).…”
Section: Introductionmentioning
confidence: 99%